Domestic accountability and ethnic reconciliation in post-war sri lanka - Nadarajah, P. (University of Jaffna, 2019)
The quest for international criminal justice before Sri Lankan domestic courts came to the foreground after the political transition in 2015. The fulfilment of this obligation may not only bring closer the process of transitional justice to the victims, Sri Lankan society and political constituencies, they may equally instil greater trust within the international community about the veracity of Sri Lanka’s commitment to ethnic reconciliation. While the new government promised a number of agendas on transitional justice reforms, they seem to be more symbolic than substantive. Taking meaningful steps towards addressing the domestic investigation of international crimes is very complex. This research paper addresses the rule of law ingredients-substantive and procedural alike-that are essential to the realization of a credible investigation into and prosecution of international crimes before Sr Lanka’s courts. This research paper highlights a number of legal, institutional, political and practical challenges in dealing with international crimes prosecution in Sri Lanka. Given the unfeasibility of a credible international crimes investigation in the present context of Sri Lanka, this article identifies in detail those fundamental rule of law areas that need restructuring in order to initiate independent and impartial domestic war crimes investigation and prosecution
Keywords: Armed conflict; Accountability; Ethnic reconciliation; State esponsibility; Transitional justice